Safety, pharmacokinetics, and food effect of sudapyridine (WX‐081), a novel anti‐tuberculosis candidate in healthy Chinese subjects - Chengyin Yu; Hongjie Qian; Qingqing Wu; Yang Zou; Qicheng Ding; Yuting Cai; Liyu Liang; Juncai Xu; Lei Li; Bin Zan; Yongguo Li; Yun Liu (Wiley, 2024)
Abstract This study aimed to assess the safety, pharmacokinetics, and food impact on sudapyridine (WX‐081), a novel drug designed to inhibit mycobacterium ATP synthase, with clinical applications for drug‐resistant tuberculosis (TB) treatment. The research comprised two arms: a single ascending dose (SAD) arm (30 to 600 mg, N = 52) and a multiple ascending dose (MAD) arm (200 to 400 mg, N = 30). The influence of food was evaluated using a 400 mg dose within an SAD cohort. Plasma concentrations of WX‐081 and M3 (main metabolite of WX‐081) were analyzed using a validated liquid‐chromatography tandem mass spectrometry method. In the SAD arm, mean residence time (MRT0‐t), terminal half‐life, and clearance of WX‐081 ranged from 18.87 to 52.8 h, 31.39 to 236.57 h, and 6.4 to 80.34 L/h, respectively. The area under the curve from time zero to the last measurable timepoint (AUC0‐t) of WX‐081 showed dose‐proportional increases in the SAD arm. The disparity between fasted and fed states of WX‐081 was significant (p < 0.05), with fed dosing resulting in a 984.07% higher AUC0‐t and 961.55% higher maximum plasma concentration. In both the SAD and MAD arms, one case each exhibited a 1 degree atrioventricular block. No QTc elongation was observed, and adverse events were not dose‐dependent. Favorable exposure, tolerability, safety, and an extended MRT0‐t suggest that WX‐081 holds promise as a phase II development candidate for drug‐resistant TB treatment.